2021
DOI: 10.1101/2021.01.08.425913
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human gut bacteria produce TH17-modulating bile acid metabolites

Abstract: The microbiota plays a pivotal role in gut immune homeostasis. Bacteria influence the development and function of host immune cells, including T helper cells expressing interleukin-17a (TH17 cells). We previously reported that the bile acid metabolite 3-oxolithocholic acid (3-oxoLCA) inhibits TH17 cell differentiation1. While it was suggested that gut-residing bacteria produce 3-oxoLCA, the identity of such bacteria was unknown. Furthermore, it was not clear whether 3-oxoLCA and other immunomodulatory bile aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Bacteroidetes species produce isoalloLCA from the gut bacterial metabolite 3-oxoLCA To identify individual gut bacterial strains that produce isoal-loLCA, we performed a screen of 990 gut bacterial isolates obtained from human stool samples (Paik et al, 2021) (Figure S1A). Single colonies were incubated for up to 96 h with either LCA or 3-oxolithocholic acid (3-oxoLCA) (100 mM), two bile acids found in the human gut (Hamilton et al, 2007;Hang et al, 2019) that we hypothesized could be precursors to isoalloLCA (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Bacteroidetes species produce isoalloLCA from the gut bacterial metabolite 3-oxoLCA To identify individual gut bacterial strains that produce isoal-loLCA, we performed a screen of 990 gut bacterial isolates obtained from human stool samples (Paik et al, 2021) (Figure S1A). Single colonies were incubated for up to 96 h with either LCA or 3-oxolithocholic acid (3-oxoLCA) (100 mM), two bile acids found in the human gut (Hamilton et al, 2007;Hang et al, 2019) that we hypothesized could be precursors to isoalloLCA (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Human gut bacteria, specifically Clostridium scindens and its close genetic relatives, convert the primary bile acid chenodeoxycholic acid (CDCA) (1) to the secondary bile acid LCA (2) through enzymes encoded by the bile-acid-inducible (bai) operon (Figure 1A) (Funabashi et al, 2020;White et al, 1980). Furthermore, in recent work, we showed that a variety of gut bacteria from the phyla Actinobacteria and Firmicutes convert LCA (2) to 3-oxoLCA (3) through the action of 3a-hydroxysteroid dehydrogenase (3a-HSDH) enzymes (Paik et al, 2021). Given our finding that gut bacteria convert 3-oxoLCA (3) to isoalloLCA (4), we hypothesized that multiple species of gut bacteria could be acting together to convert the host-produced bile acid CDCA to isoalloLCA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations